Analysis of blockchain law and regulations - P Triveni; Jaikishen; R Sanjana (ITM Web of Conferences)
Blockchain technology has brought significant innovation to various industries, including healthcare, supply chain, finance, and more. However, rapid adoption of the blockchain technology has outpaced the development of comprehensive legal frameworks, resulting in a complex and fragmented regulatory landscape. This paper aims to analyse current blockchain laws and regulations globally, identify the challenges faced in regulating blockchain, and propose potential solutions to harmonize these regulations to foster innovation while ensuring legal compliance and consumer protection. Key words: Block Chain technology, Legal framework, Regulations, Cryptocurrency